Methods of Working with Exercises in Teaching A Foreign Language - Suyundukova Gulchexra Sa'dullayeva; Mustafaqulova Nasiba Ashiraliyevna (Genius Publishing Group, 2022)
In this article, an attempt was made to provide scientific information on the topic of exercise-related techniques in teaching a foreign language.
Keywords: Non-speech exercises; phonetic; grammatic and lexical exercises; creative speech exercises